Dark matter from primordial black holes would hold charge. Issue 2 (1st February 2023) - Araya, I.J.; Padilla, N.D.; Rubio, M.E.; Sureda, J.; Magaña, J.; Osorio, L.
Abstract: We explore the possibility that primordial black holes (PBHs) contain electric charge down to the present day. We find that PBHs should hold a non-zero net charge at their formation, due to either Poisson fluctuations at horizon crossing or high-energy particle collisions. Although initial charge configurations are subject to fast discharge processes through particle accretion or quantum particle emission, we show that maximally rotating PBHs could produce magnetic fields able to shield them from discharge. Moreover, given that electrons are the lightest and fastest charge carriers, we show that the plasma within virialised dark matter haloes can endow PBHs with net negative charge. We report charge-to-mass ratios between 10 -31 C /kg and 10 -15 C /kg for PBHs within the mass windows that allow them to constitute the entirety of the dark matter in the Universe.